2017
DOI: 10.1159/000484620
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Efficacy, Safety, and Biomarkers for Second-Line Axitinib in Patients with Advanced Hepatocellular Carcinoma: From a Randomized Phase II Study

Abstract: Background: An unmet need exists for treatment of patients with advanced hepatocellular carcinoma (HCC) who progress on or are intolerant to sorafenib. A global randomized phase II trial (ClinicalTrial.gov No. NCT01210495) of axitinib, a vascular endothelial growth factor receptor 1-3 inhibitor, in combination with best supportive care (BSC) did not prolong overall survival (OS) over placebo/BSC, but showed improved progression-free survival in some patients. Subgroup analyses were conducted to identify potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In a randomized phase 2 trial in advanced HCC, second-line treatment with axitinib plus best supportive care resulted in significantly longer PFS and time to progression and a higher clinical benefit rate versus placebo plus best supportive care, with an acceptable safety profile [32]. Although the primary OS endpoint had not been met in this study, a subset of Japanese patients showed favorable OS outcomes compared with patients from other countries [33].…”
Section: Introductionmentioning
confidence: 75%
“…In a randomized phase 2 trial in advanced HCC, second-line treatment with axitinib plus best supportive care resulted in significantly longer PFS and time to progression and a higher clinical benefit rate versus placebo plus best supportive care, with an acceptable safety profile [32]. Although the primary OS endpoint had not been met in this study, a subset of Japanese patients showed favorable OS outcomes compared with patients from other countries [33].…”
Section: Introductionmentioning
confidence: 75%
“…In this series of 202 patients, 78 non-Asian and 124 Asian, no significant differences in OS were found according to location of enrollment. However, in an exploratory analysis excluding patients intolerant to prior antiangiogenic therapy, axitinib showed favorable OS in Asians, especially Japanese patients (18). No difference in safety profile was observed on regional basis.…”
mentioning
confidence: 89%
“…Therefore, the authors concluded that axitinib may represent a valuable option in a subgroup of Japanese patients that excludes sorafenib-intolerant subjects; moreover, several potential biomarkers might help the clinician in selecting a subgroup of patients more likely to benefit from axitinib therapy (18).…”
Section: Editorial Commentarymentioning
confidence: 99%
See 2 more Smart Citations